RNA modifications: emerging players in the regulation of reproduction and development - Wen Junfei; Zhu Qifan; Liu Yong; Gou Lan-Tao (Acta Biochimica et Biophysica Sinica)
The intricate world of RNA modifications, collectively termed the epitranscriptome, covers over 170 identified modifications and impacts RNA metabolism and, consequently, almost all biological processes. In this review, we focus on the regulatory roles and biological functions of a panel of dominant RNA modifications (including m6A, m5C, Ψ, ac4C, m1A, and m7G) on three RNA types—mRNA, tRNA, and rRNA—in mammalian development, particularly in the context of reproduction as well as embryonic development. We discuss in detail how those modifications, along with their regulatory proteins, affect RNA processing, structure, localization, stability, and translation efficiency. We also highlight the associations among dysfunctions in RNA modification-related proteins, abnormal modification deposition and various diseases, emphasizing the roles of RNA modifications in critical developmental processes such as stem cell self-renewal and cell fate transition. Elucidating the molecular mechanisms by which RNA modifications influence diverse developmental processes holds promise for developing innovative strategies to manage developmental disorders. Finally, we outline several unexplored areas in the field of RNA modification that warrant further investigation.